2020
DOI: 10.1136/bmjgh-2019-002273
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of health and health-related sustainable development goals: progress, challenges and opportunities – a systematic literature review

Abstract: IntroductionWhile health is one of the Sustainable Development Goals (SDGs), many other ‘health-related’ goals comprise determinants of health. Integrated implementation across SDGs is needed for the achievement of Agenda 2030. While existing literature is rich in normative recommendations about potentially useful approaches, evidence of implementation strategies being adopted by countries is limited.MethodsWe conducted a systematic review with qualitative synthesis of findings using peer reviewed and grey lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…2020 has shown that the key issues challenging the achievement of SDG3 are a lack of financing. This is not a new problem as the limited financial resources (allocated by the government to the implementation of health-related sustainable development goals) is one of the most mentioned challenges in the academic literature (Aftab et al, 2020;Georgeson & Maslin, 2018;Siddiqi et al, 2020). As the number of large out-of-pocket expenses has increased and will continue to increase in the future, the United Nations has reported that the achievement of universal healthcare coverage remains a global challenge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2020 has shown that the key issues challenging the achievement of SDG3 are a lack of financing. This is not a new problem as the limited financial resources (allocated by the government to the implementation of health-related sustainable development goals) is one of the most mentioned challenges in the academic literature (Aftab et al, 2020;Georgeson & Maslin, 2018;Siddiqi et al, 2020). As the number of large out-of-pocket expenses has increased and will continue to increase in the future, the United Nations has reported that the achievement of universal healthcare coverage remains a global challenge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this share varies from country to country [41], being low in the countries of Central and Eastern Europe [42,43], and this is not conducive to addressing social inequalities, including in public health [44]. This makes the connection between health and elements of sustainable development increasingly clear [45]. The SD approach allows for a holistic view of all causes of adverse health effects [46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several of these interrelated issues to which nations worldwide have committed are summarised in the Agenda 2030 sustainable development goals [9,10,30,31] and included in the definition of 'global health' and 'global nursing' proposed by Wilson et al [3]. The strategic connections between global health and sustainability are also highlighted in Sweden [32].…”
Section: The Relation Between Environmental Determinants Of Health and Equitymentioning
confidence: 99%